2005
DOI: 10.1111/j.1440-172x.2005.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

‘They survive despite the organizational culture, not because of it’: A longitudinal study of new staff perceptions of what constitutes support during the transition to an acute tertiary facility

Abstract: Increasing difficulties of recruitment and retention of nursing staff strongly indicate that organizations should identify factors that contribute to successful transition of new staff to the workplace. Although many studies have identified problems facing new staff, fewer studies have articulated best practices. The purpose of this longitudinal study was to ascertain what new staff perceived as supportive elements implemented by the organization to assist their integration. Sixteen staff in Phase I and 12 sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 11 publications
2
43
0
Order By: Relevance
“…Survival in the 'deep end' requires that the new nurse identify the 'goodies from the baddies' (Fox et al 2005). Despite literature declaring the custom of 'throwing new graduates in at the deep end' as being unrealistic and ineffective, the data suggests that the practice continues to be reinforced in nursing (Maben & Clark 1998, Gerrish 2000, Amos 2001, De Bellis et al 2001.…”
Section: Discussionmentioning
confidence: 98%
“…Survival in the 'deep end' requires that the new nurse identify the 'goodies from the baddies' (Fox et al 2005). Despite literature declaring the custom of 'throwing new graduates in at the deep end' as being unrealistic and ineffective, the data suggests that the practice continues to be reinforced in nursing (Maben & Clark 1998, Gerrish 2000, Amos 2001, De Bellis et al 2001.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent to this, in the 1990s, roles around supporting learners have been more extensively reported (Saarikoski et al, 2007). However, despite the discussions around how nurses can support learners, studies indicate that they do not always readily engage in behaviours that facilitate integration of the learner nor do they provide effective feedback for continuing development of the learner (Fox et al, 2005;Hamshire et al, 2012). Such findings indicate that insufficient provision has been made for behaviours that are crucial to maximising learning, to routinely be incorporated into practice.…”
Section: Introductionmentioning
confidence: 90%
“…For example, if continuity of nurse-new graduate, or nurse-student is desired, as is the case with preceptoring and mentoring then rostering needs to be considered to ensure shifts are the same, and commenced at the best time for handover and receiving of information (Fox et al, 2005). Work allocation also needs to be planned to ensure the nature of the work, where appropriate, can be easily observed and the learner can safely constructively participate in care delivery.…”
Section: Effective Management Of Workloadmentioning
confidence: 97%
See 1 more Smart Citation
“…One study reported that while most respondents had been allocated mentors less than half were satisfied with their relationships and approximately one-third responded that they were dissatisfied (Parker et al, 2013). Reasons for the preceptorship not working include: attitudes of preceptors; preceptorepreceptee not being rostered together, inappropriate skill mix such that the preceptor is a team leader or managing other junior staff, inappropriate RN being allocated to precept or preceptor's misunderstanding of the role they have been asked to fulfil (Cubit and Ryan, 2011;Henderson and Eaton, 2013;Fox et al, 2005;Johnstone et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 96%